Student Interest in Physics Subject at the Senior High School Level in Gunungsitoli City - Envilwan Berkat Harefa (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to determine how interested high school students in Gunungsitoli City are in physics subjects. Interest in learning has an impact on learning outcomes. Someone who has no interest in certain subjects will have difficulty achieving optimal learning outcomes. The research method used is quantitative descriptive in the form of a physics learning interest questionnaire by distributing questionnaires to respondents directly via online (google form). Data collection was carried out by a sample of students majoring in science at Gunungsitoli City High School class X and class XI. In accordance with the analysis technique used, the data that has been collected is recapitulated according to the appropriate indicators. The population in this study were Gunungsitoli High School students. The research results show that high school students in Gunungsitoli City have a good interest in studying physics with an overall percentage of 79.77%. The highest percentage of statements of interest from high school students in Gunungsitoli City was in the aspect of the statement "Physics teachers who teach are very enjoyable" at 92.17%. The lowest percentage of expressions of interest for high school students in Gunungsitoli City was in the aspect of the statement "Physics cannot help you achieve great success" at 44.35%. The results of the research show that students at Gunungsitoli City High School are more likely to have a good response to physics learning seen from the percentage of filling out the interest questionnaire.